Ammonia sensor based on PANI@g-C3N4 nanocomposite material and its preparation method and application
By using PANI@g-C3N4 nanocomposites and combined with improved preparation methods, stable p-n heterojunctions are formed, which solves the problem of high-temperature operation and insufficient mechanical strength of polyaniline materials, and achieves efficient detection of low-concentration ammonia gas at room temperature.
Patent Information
- Application Number
- CN202210344185.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-03-31
AI Technical Summary
Existing ammonia sensors require high temperature operation, resulting in high energy consumption and limited practical application, and the mechanical strength of polyaniline materials is insufficient, making it difficult to maintain effectiveness in long-term testing.
The PANI@g-C3N4 nanocomposite material based on π-π conjugation was adopted to prepare g-C3N4 two-dimensional sheet material by improved one-step calcination method and hydrothermal method, and was compounded with PANI by in-situ chemical oxidation polymerization to form a stable p-n heterojunction to improve gas-sensitive performance.
It realizes stable detection of low concentration ammonia gas at room temperature, the detection limit can reach 2ppm level, and the material has good toughness, which is suitable for integrated components.
Smart Images

Figure CN114778612B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensors and environmental monitoring, and specifically relates to a resistive ammonia sensor based on a PANI@g-C3N4 nanocomposite material with enhanced gas-sensitive performance through a π-π conjugated stable pn heterojunction, a preparation method thereof, and an application of ammonia detection at room temperature. Background Art
[0002] Since Fritz Haber proposed the industrial production method of ammonia in 1905, ammonia, as one of the most produced chemical raw materials, has been widely used in agriculture, industry, pharmaceuticals and other fields, greatly promoting the development of science and technology. Fritz Haber also won the 1918 Nobel Prize in Chemistry. However, ammonia, as a toxic and harmful gas, always threatens the life, health and safety of people who come into contact with it. According to the U.S. Occupational Safety and Health Administration (OSHA), the upper limit of ammonia concentration in an 8-hour shift workplace is 25ppm, and the upper limit of ammonia concentration in the short term (15 minutes) is 35ppm. my country's GB50096-2011 "Residential Design Code" also sets the indoor ammonia concentration to be less than 0.2mg·m -3 (about 0.26ppm). Since ammonia is well soluble in water, ammonia in the air will adsorb on the conjunctiva of the eye, causing redness and itching of the eyes and even damage vision. Secondly, ammonia will irritate the respiratory mucosa and cilia, leading to symptoms such as sore throat, cough, and hoarseness. On the other hand, as a component of oral exhaled air, an increase in the proportion of ammonia can be a clinical manifestation of renal failure and hepatic encephalopathy.
[0003] At present, the main means of detecting ammonia include optical analysis, chemical method, gas chromatography, X-ray photoelectron spectroscopy, sensor method, etc. The sensor method has been widely used due to its simple preparation process and good gas-sensitive signal transmission. The sensitive materials of ammonia sensors are mainly metal oxide semiconductors, which need to reach a certain working temperature (250-400°C) when detecting gases. However, with the development of sensors in wearable devices and integrated components, the working characteristics of metal oxide semiconductors that need to respond at high temperatures have increased energy consumption and limited the practical application of ammonia sensors. Therefore, it is of great significance and research value to develop an ammonia sensor with a low detection limit, easy to carry, and room temperature response.
[0004] Polyaniline (PANI), a P-type semiconductor material that transfers carriers through delocalized π bonds, exhibits good gas-sensing performance for ammonia detection at room temperature. However, PANI also faces the challenge of weak mechanical strength and easy failure in long-term testing. Therefore, the preparation of PANI composite materials with good gas-sensing and mechanical properties has become an important topic that needs to be studied urgently.
[0005] g-C3N4 is a typical polymer n-type semiconductor. The C and N atoms in its structure form a highly delocalized π-conjugated system through sp2 hybridization. It is a nitrogen-doped two-dimensional carbon-based graphene-like material with a unique structure. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide an ammonia sensor based on PANI@g-C3N4 nanocomposite material, a preparation method thereof and an application thereof for realizing stable detection of low-concentration ammonia at room temperature. The present invention firstly prepares a porous NaCO3 / Bulk-C3N4 composite by adding bicarbonate as a foaming agent and a soft film plate to nitrogen-containing organic matter through an improved one-step calcination method, and then obtains a g-C3N4 two-dimensional sheet material by exfoliation through a hydrothermal method, and then composites the g-C3N4 two-dimensional sheet material with PANI through an in-situ chemical oxidation polymerization method. The g-C3N4 sheet material is successfully regulated by using the g-C3N4 sheet structure during polymerization, and the agglomeration of PANI is reduced. Secondly, the pn heterojunction with a stable π~π conjugated structure formed at the interface of g-C3N4 and PANI is very beneficial to the transfer of carriers. Therefore, the ammonia sensor of the PANI@g-C3N4 nanocomposite material prepared by the present invention has good gas-sensitive performance to ammonia.
[0007] The object of the present invention is to achieve the following:
[0008] The present invention provides a method for preparing an ammonia sensor based on a PANI@g-C3N4 nanocomposite material, which mainly comprises the following steps:
[0009] (1) adding nitrogen-containing organic matter and bicarbonate to water in a mass ratio of 1:2 to 2:1 and mixing to form a paste, drying to remove water, calcining at 400 to 550° C. for 1 to 4 hours, and cooling to room temperature to obtain carbonate / bulk-C3N4;
[0010] (2) dispersing the carbonate / bulk-C3N4 obtained in step (1) in an ammonia solution, stirring evenly and transferring to a hydrothermal reactor, keeping the temperature at 160°C to 180°C for 12h to 18h, collecting the precipitate after the hydrothermal reaction, drying it, keeping the temperature at 200°C to 280°C under an inert atmosphere for 1 to 4h, cooling it to room temperature, washing it with water to remove the remaining salt, and drying it to obtain a g-C3N4 two-dimensional sheet material;
[0011] (3) dispersing aniline and the g-C3N4 two-dimensional sheet material obtained in step (2) in an acidic solution at a mass ratio of 1:2 to 2:1, stirring continuously in an ice bath, and adding an aqueous solution of ammonium persulfate dropwise until the reaction solution changes from a light yellow suspension to a blue suspension, and then stopping the addition to obtain a suspension of PANI@g-C3N4 ammonia gas-sensitive material;
[0012] (4) Take the interdigital electrode, treat its substrate so that the surface of the substrate is negatively charged, and then immerse the treated interdigital electrode in the suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 10 to 60 minutes, take out the interdigital electrode, wash it with an acidic solution, and obtain an ammonia sensor after drying.
[0013] Preferably, the nitrogen-containing organic matter in step (1) includes urea, melamine, and thiourea; and the bicarbonate includes sodium bicarbonate and potassium bicarbonate.
[0014] Preferably, the mass ratio of the nitrogen-containing organic matter to the bicarbonate in step (1) is 1:1 to 2:1.
[0015] Preferably, the calcination in step (1) is carried out in a muffle furnace under air atmosphere, with a heating rate of 1 to 5°C / min.
[0016] Preferably, the optimum temperature for calcination in step (1) is 480° C. and the calcination time is 2 h.
[0017] Preferably, the concentration of the ammonia solution in step (2) is 0.8 mol / L to 2.4 mol / L, and the mass volume ratio of carbonate / Bulk-C3N4 and ammonia solution is 2 to 100 g / L.
[0018] Preferably, the inert atmosphere in step (2) includes nitrogen, neon, argon and helium.
[0019] Preferably, the concentration of the acidic solution in step (3) is 0.1 to 3 mol / L, and the mass volume ratio of aniline to the acidic solution is 1 to 100 g / L.
[0020] Preferably, the concentration of the aqueous ammonium persulfate solution in step (3) is 0.1 to 1 g / mL.
[0021] Preferably, the interdigitated electrodes described in step (4) are Au interdigitated electrodes, and the substrate of the Au interdigitated electrodes is a polyimide substrate with a substrate size of 5 mm*10 mm, with a total of 7 pairs of interdigitated electrodes.
[0022] Preferably, the specific process of substrate treatment in step (4) is to completely immerse the substrate of the interdigitated electrode in a polydiallyldimethylammonium chloride aqueous solution with a mass concentration of 0.5-2% and a poly(4-styrene sodium sulfonate) aqueous solution with a mass concentration of 1-5% in turn, so that the surface is negatively charged.
[0023] Another aspect of the present invention provides an ammonia sensor prepared by the above preparation method, wherein the ammonia sensor is a resistive ammonia sensor.
[0024] The present invention also provides application of the above-mentioned ammonia sensor in detecting ammonia at room temperature.
[0025] The beneficial effects of the present invention compared with the prior art are as follows:
[0026] 1. The carbon nitride prepared by the present invention using sodium bicarbonate as a foaming agent and a soft film board has the characteristics of being porous and having a large surface area, which provides favorable conditions for subsequent stripping; the gaseous stripping method using sodium carbonate and ammonia water has sufficient gas production, a low stripping temperature, energy saving, and a good stripping effect; the g-C3N4 two-dimensional sheet material is composited with PANI by an in-situ chemical oxidation polymerization method, and a pn heterojunction with a stable π~π conjugated structure formed at the interface of g-C3N4 and PANI is very beneficial to the transfer of carriers. The PANI@g-C3N4 sensing material prepared by the present invention has good gas-sensitive properties, has a good response to low-concentration ammonia at room temperature, and the detection limit can reach 2ppm level, which is in line with the current development direction of sensors towards integration and room temperature response.
[0027] 2. The ammonia sensor of the present invention is prepared on the Au cross electrode of the polyimide (PI) substrate, and the prepared ammonia sensor of the PANI@g-C3N4 nanocomposite material has good toughness.
[0028] 3. The ammonia sensor of the present invention is a resistive ammonia sensor. The polyaniline molecules are protonated by acid. When exposed to air, the adsorption / desorption process of ammonia will change the conductivity of PANI. The low-resistance emerald salt (ES) of PANI will be transformed into the high-resistance emerald base (EB). When the ammonia concentration decreases, ammonia will be desorbed from the polyaniline molecular chain, and the polyaniline will return to the low-resistance state. Thus, the response to ammonia is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0030] Figure 1 The preparation flow chart of ammonia gas sensor based on PANI@g-C3N4 nanocomposite;
[0031] Figure 2 The scanning electron microscope (SEM) image of Bulk-C3N4 nanoparticles prepared in Example 1;
[0032] Figure 3 This is a scanning electron microscope (SEM) image of g-C3N4 nanoparticles prepared in Example 1;
[0033] Figure 4 This is a scanning electron microscope (SEM) image of the PANI@g-C3N4 nanocomposite prepared in Example 1;
[0034] Figure 5 This is a transmission electron microscope (TEM) image of the PANI@g-C3N4 nanocomposite prepared in Example 1;
[0035] Figure 6 X-ray diffraction (XRD) images of g-C3N4, Bulk-C3N4, PANI and PANI@g-C3N4 nanomaterials prepared in Example 1;
[0036] Figure 7 Response recovery curves of the ammonia sensors prepared in Example 1 and Comparative Example 1 when exposed to NH3 at different concentrations. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.
[0038] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0039] Embodiment 1:
[0040] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0041] (1) 5 g of melamine and 2.5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60° C. for 5 h in a drying oven to evaporate the water. The mixture was kept at 480° C. for 2 h in a muffle furnace and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0042] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (0.8 mol / L), and the mixture was transferred to a hydrothermal reactor after continuous stirring for 30 min. The mixture was placed in a thermostat at 180 °C for 12 h. After the hydrothermal reaction, the precipitate was collected and placed in a drying oven at 60 °C for 12 h. The precipitate was placed in a tubular furnace under N2 atmosphere and kept at 230 °C for 2 h, and then naturally cooled to room temperature. The mixture was washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a two-dimensional sheet material of g-C3N4.
[0043] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.5 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. An aqueous solution of ammonium persulfate (APS) (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0044] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0045] Embodiment 2:
[0046] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0047] (1) 5 g of melamine and 2.5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60° C. for 5 h in a drying oven to evaporate the water. The mixture was kept at 480° C. for 2 h in a muffle furnace and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0048] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (1.6 mol / L), and the mixture was transferred to a hydrothermal reactor after continuous stirring for 30 min. The mixture was placed in a thermostat at 180 °C for 12 h. After the hydrothermal reaction, the precipitate was collected and placed in a drying oven at 60 °C for 12 h. The precipitate was placed in a tubular furnace under N2 atmosphere at 230 °C for 2 h, and then naturally cooled to room temperature. The mixture was washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a two-dimensional sheet material of g-C3N4.
[0049] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.25 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0050] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0051] Embodiment 3:
[0052] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0053] (1) 5 g of melamine and 2.5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60° C. for 5 h in a drying oven to evaporate the water. The mixture was kept at 480° C. for 2 h in a muffle furnace and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0054] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (2.4 mol / L), stirred continuously for 30 min, and then transferred to a hydrothermal reactor, placed in a thermostat at 180 °C, and kept warm for 12 hours. After the hydrothermal process, the precipitate was collected and placed in a drying oven at 60 °C for 12 hours. The obtained precipitate was placed in a tubular furnace under N2 atmosphere and kept warm at 230 °C for 2 hours, and then naturally cooled to room temperature; washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a g-C3N4 two-dimensional sheet material;
[0055] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 1 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0056] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0057] Embodiment 4:
[0058] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0059] (1) 5 g of melamine and 5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60°C in a drying oven for 5 h to evaporate the water, and then kept at 480°C in a muffle furnace for 2 h. The mixture was cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0060] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (0.8 mol / L), and the mixture was transferred to a hydrothermal reactor after continuous stirring for 30 min. The mixture was placed in a thermostat at 180 °C for 12 h. After the hydrothermal reaction, the precipitate was collected and placed in a drying oven at 60 °C for 12 h. The precipitate was placed in a tubular furnace under N2 atmosphere and kept at 230 °C for 2 h, and then naturally cooled to room temperature. The mixture was washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a two-dimensional sheet material of g-C3N4.
[0061] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 1 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0062] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0063] Embodiment 5:
[0064] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0065] (1) 5 g of melamine and 5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60°C in a drying oven for 5 h to evaporate the water. The mixture was kept at 550°C in a muffle furnace for 2 h and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0066] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (1.6 mol / L), stirred continuously for 30 min, and then transferred to a hydrothermal reactor, placed in a thermostat at 180 °C, and kept warm for 12 hours. After the hydrothermal process, the precipitate was collected and placed in a drying oven at 60 °C for 12 hours. The obtained precipitate was placed in a tubular furnace under N2 atmosphere and kept warm at 230 °C for 2 hours, and then naturally cooled to room temperature; washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a g-C3N4 two-dimensional sheet material;
[0067] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.5 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0068] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0069] Embodiment 6:
[0070] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0071] (1) 5 g of melamine and 5 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60°C in a drying oven for 5 h to evaporate the water. The mixture was kept at 480°C in a muffle furnace for 2 h and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0072] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (2.4 mol / L), stirred continuously for 30 min, and then transferred to a hydrothermal reactor, placed in a thermostat at 180 °C, and kept warm for 12 hours. After the hydrothermal process, the precipitate was collected and placed in a drying oven at 60 °C for 12 hours. The obtained precipitate was placed in a tubular furnace under N2 atmosphere and kept warm at 230 °C for 2 hours, and then naturally cooled to room temperature; washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a g-C3N4 two-dimensional sheet material;
[0073] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.25 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0074] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0075] Embodiment 7:
[0076] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0077] (1) 5 g of melamine and 10 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60 °C in a drying oven for 5 h to evaporate the water, kept at 480 °C in a muffle furnace for 2 h, and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0078] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (0.8 mol / L), and the mixture was transferred to a hydrothermal reactor after continuous stirring for 30 min. The mixture was placed in a thermostat at 180 °C for 12 h. After the hydrothermal reaction, the precipitate was collected and placed in a drying oven at 60 °C for 12 h. The precipitate was placed in a tubular furnace under N2 atmosphere and kept at 230 °C for 2 h, and then naturally cooled to room temperature. The mixture was washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a two-dimensional sheet material of g-C3N4.
[0079] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.25 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0080] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0081] Embodiment 8:
[0082] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0083] (1) 5 g of melamine and 10 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60°C in a drying oven for 5 h to evaporate the water, and then kept at 480°C in a muffle furnace for 2 h. The mixture was cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0084] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (1.6 mol / L), stirred continuously for 30 min, and then transferred to a hydrothermal reactor, placed in a thermostat at 180 °C, and kept warm for 12 hours. After the hydrothermal process, the precipitate was collected and placed in a drying oven at 60 °C for 12 hours. The obtained precipitate was placed in a tubular furnace under N2 atmosphere and kept warm at 230 °C for 2 hours, and then naturally cooled to room temperature; washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a g-C3N4 two-dimensional sheet material;
[0085] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 1 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0086] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0087] Embodiment 9:
[0088] A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material comprises the following steps:
[0089] (1) 5 g of melamine and 10 g of sodium bicarbonate were mixed into 8 ml of deionized water and stirred into a paste as a precursor. The mixture was kept at 60° C. for 5 h in a drying oven to evaporate the water. The mixture was kept at 550° C. for 2 h in a muffle furnace and then cooled to room temperature to obtain a light yellow powder NaCO3 / Bulk-C3N4.
[0090] (2) Exfoliation of Bulk-C3N4 by hydrothermal method: 2 g NaCO3 / Bulk-C3N4 was dispersed in 100 ml ammonia solution (2.4 mol / L), stirred continuously for 30 min, and then transferred to a hydrothermal reactor, placed in a thermostat at 180 °C, and kept warm for 12 hours. After the hydrothermal process, the precipitate was collected and placed in a drying oven at 60 °C for 12 hours. The obtained precipitate was placed in a tubular furnace under N2 atmosphere and kept warm at 230 °C for 2 hours, and then naturally cooled to room temperature; washed three times with deionized water to remove the remaining sodium salt, and dried to obtain a g-C3N4 two-dimensional sheet material;
[0091] (3) PANI@g-C3N4 ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), followed by the addition of 0.5 g g-C3N4 two-dimensional sheet material, and the mixture was stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution changed from a light yellow suspension to a blue suspension, and then the addition was stopped.
[0092] (4) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0093] Comparative Example 1:
[0094] A method for preparing an ammonia sensor based on PANI comprises the following steps:
[0095] (1) PANI ammonia gas-sensitive material was prepared by in-situ chemical oxidation polymerization: 0.5 g aniline was dispersed in 100 ml dilute hydrochloric acid (2 mol / L), and stirred continuously in an ice bath. APS (ammonium persulfate) aqueous solution (0.2 g / L) precooled at 4 °C was added dropwise until the reaction solution turned into a blue suspension, and then the addition was stopped.
[0096] (2) Preparation of PANI@g-C3N4 thin film sensor by electrostatic self-assembly: The polyimide (PI) substrate of the Au interdigital electrode was completely immersed in an aqueous solution of polydiallyldimethylammonium chloride (PDDA) and an aqueous solution of poly (4-styrenesulfonate) (PSS) successively to make the surface negatively charged, and then the treated interdigital electrode was immersed in a suspension of the PANI ammonia gas-sensitive material prepared in step (1) for 30 min. The Au interdigital electrode was taken out, washed with dilute hydrochloric acid (1.5-2 mol / L), and dried at 80°C overnight to obtain an ammonia sensor.
[0097] Effect example:
[0098] The response of the ammonia sensor of the PANI@g-C3N4 nanocomposite material of Example 1 and the PANI ammonia sensor of Comparative Example 1 to different gradient concentrations of ammonia at room temperature, the response value S of the gas sensor is defined as: Response% = (Rg-Ra) / Ra×100%, R a and R g They are the resistance values of the interdigital electrodes when the sensor is in air and in a certain concentration of NH3. The test results are as follows Figure 7As shown, it can be seen that the response value of the ammonia sensor of the PANI@g-C3N4 nanocomposite material of the present invention shows a trend of gradually increasing with the increase of ammonia concentration, and the response value is significantly better than that of the PANI ammonia sensor of Comparative Example 1. It shows good stability, relatively fast response and recovery, and relatively consistent fall-back baseline in the 2-100ppm ammonia cyclic gradient test, and is an ideal ammonia sensor for realizing room temperature ammonia detection.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an ammonia sensor based on PANI@g-C3N4 nanocomposite material, characterized in that: The following steps are involved: (1) adding nitrogen-containing organic matter and bicarbonate to water in a mass ratio of 1:2 to 2:1 and mixing to form a paste, drying to remove water, calcining at 400 to 550° C. for 1 to 4 h, and cooling to room temperature to obtain carbonate / Bulk-C3N4; (2) dispersing the carbonate / bulk-C3N4 obtained in step (1) in an ammonia solution, stirring evenly and transferring to a hydrothermal reactor, keeping the temperature at 160°C to 180°C for 12h to 18h. After the hydrothermal reaction, keeping the obtained precipitate at 200°C to 280°C under an inert atmosphere for 1h to 4h, and cooling to room temperature to obtain a g-C3N4 two-dimensional sheet material; (3) dispersing aniline and the g-C3N4 two-dimensional sheet material obtained in step (2) in an acidic solution at a mass ratio of 1:2 to 2:1, stirring continuously in an ice bath, and dropping an aqueous solution of ammonium persulfate until the reaction solution changes from a light yellow suspension to a blue suspension, and then stopping the dropping to obtain a suspension of PANI@g-C3N4 ammonia gas-sensitive material; (4) taking an interdigital electrode, treating its substrate so that the surface of the substrate is negatively charged, and then immersing the treated interdigital electrode in the suspension of the PANI@g-C3N4 ammonia gas-sensitive material prepared in step (3) for 10 to 60 minutes, taking out the interdigital electrode, and drying it to obtain an ammonia sensor; In step (1), the nitrogen-containing organic matter includes urea, melamine, and thiourea; the bicarbonate includes sodium bicarbonate and potassium bicarbonate; The concentration of the ammonia solution in step (2) is 0.8 mol / L~2.4 mol / L, and the mass volume ratio of carbonate / Bulk-C3N4 and ammonia solution is 2~100 g / L.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of nitrogen-containing organic matter to bicarbonate is 1:1 to 2:
1.
3. The preparation method according to claim 1, characterized in that: The calcination in step (1) is carried out in a muffle furnace under air atmosphere, with a heating rate of 1-5°C / min; the calcination temperature is 480°C and the calcination time is 2h.
4. The preparation method according to claim 1, characterized in that: The inert atmosphere in step (2) includes nitrogen, neon, argon and helium.
5. The preparation method according to claim 1, characterized in that The concentration of the acidic solution in step (3) is 0.1-3 mol / L, and the mass volume ratio of aniline to the acidic solution is 1-100 g / L.
6. The preparation method according to claim 1, characterized in that: The concentration of the ammonium persulfate aqueous solution described in step (3) is 0.1~1g / mL.
7. The preparation method according to claim 1, characterized in that: The interdigitated electrodes described in step (4) are Au interdigitated electrodes, and the substrate of the Au interdigitated electrodes is a polyimide substrate with a substrate size of 5 mm*10 mm, with a total of 7 pairs of interdigitated electrodes.
8. The preparation method according to claim 1, characterized in that: The specific process of substrate treatment in step (4) is to completely immerse the substrate of the interdigitated electrode in a polydiallyldimethylammonium chloride aqueous solution with a mass concentration of 0.5-2% and a poly(4-styrene sodium sulfonate) aqueous solution with a mass concentration of 1-5% in turn, so that the surface is negatively charged.
9. The ammonia sensor prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The ammonia sensor is a resistive ammonia sensor.
10. Use of the ammonia sensor according to claim 9 for detecting ammonia at room temperature.
Citation Information
Patent Citations
Preparation method of ammonia gas sensor based on polyaniline-vanadium carbide and as detection system and application of ammonia gas sensor
CN111307883A